2018
DOI: 10.1055/s-0038-1641155
|View full text |Cite
|
Sign up to set email alerts
|

Previous History of Breast Cancer Increases Rates of Pulmonary Embolism and Costs after Total Knee Arthroplasty: An Evaluation of 185,114 Matched Patients

Abstract: Risk factors for adverse events after total knee arthroplasty (TKA) relating to malignancy have not been well studied. Thus, the purpose of this study was to conduct a retrospective case-control outcome and cost analysis after TKA in this population. Patients with a history of breast cancer (BrCa) were identified based on the International Classification of Disease 9th revision codes. An age- and sex-matched cohort was also identified of patients without a history of BrCa. Complications, length of stay, comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our findings of 1.44 vs. 0.4% (PCa vs. without PCa, respectively) PE rates in these cohorts are similar to what has been reported in the literature for patients with breast cancer (0.56% without and 0.65% with a history of breast cancer). 8 Nonetheless, the difference seen here of more than 3x the incidence should be highlighted and further studied. In the initial article evaluating outcomes of TKA/total hip arthroplasty (THA) patients with a history of malignancy, Karam et al reported a comparable difference in PE rates to the one seen here, with a 1.36% incidence of those with a history of cancer versus 1.05% in those without, although their sample size was far more heterogenous (including THA/TKA, revision and bilateral procedures, history, and active malignancy and various types of malignancies among other) and smaller to ours (n ¼ 26,415).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Our findings of 1.44 vs. 0.4% (PCa vs. without PCa, respectively) PE rates in these cohorts are similar to what has been reported in the literature for patients with breast cancer (0.56% without and 0.65% with a history of breast cancer). 8 Nonetheless, the difference seen here of more than 3x the incidence should be highlighted and further studied. In the initial article evaluating outcomes of TKA/total hip arthroplasty (THA) patients with a history of malignancy, Karam et al reported a comparable difference in PE rates to the one seen here, with a 1.36% incidence of those with a history of cancer versus 1.05% in those without, although their sample size was far more heterogenous (including THA/TKA, revision and bilateral procedures, history, and active malignancy and various types of malignancies among other) and smaller to ours (n ¼ 26,415).…”
Section: Discussionmentioning
confidence: 73%
“…Similar to our findings here, we have found that breast cancer in TKA also increased the 90day reimbursement rates and as such believe that accounting for this comorbidity warrants further research. [7][8][9]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1974, the first patellar replacement was introduced as well as joint surface replacing. After that, scientists developed the method of installing prosthesis with bone-cement and retaining anterior and posterior cruciate ligaments [8].…”
Section: Introductionmentioning
confidence: 99%